The opportunities and challenges of ecotourism development with special reference to Assam (International Journal of Food and Nutritional Sciences, 2023)
Ecotourism is a new form of tourism based on the idea of sustainability. The concept of ecotourism came into prominence in the late 80s as a strategy for reconciling conservation with development in ecologically rich areas. The concept of ecotourism has become popular probably due to the wide spread and growing interests in the natural environment and the corresponding recognition of the importance of conserving natural environmental quality. Characteristically, ecotourism involves a kind of tourist activity that has a minimal impact on the natural and socio-cultural environment. It helps contribute directly to conservation and is especially instrumental in protecting precious diversity of species in biodiversity rich areas. Conservation of natural resources prevents environmental degradation. That is why; this form of tourism has received global importance. It is currently recognized as the fastest growing segment of the tourism market. Assam- the gateway to the North East India is a hotspot for tourists due to its natural beauty and favourable climate. This paper is an attempt to introduce the major eco-tourism prospects of Assam and their role in conserving the environment.